The application of oil palm tissue culture and its challenges in Malaysia – a review / Mohamad Amirul Jefni Nasaruddin - Nasaruddin, Mohamad Amirul Jefni (Faculty of Plantation and Agrotechnology, 2019)
The oil palm, Elaeis guineensis is originating from West Africa and the main palm belt ran from Sierra Leone, Ghana, the Ivory Coast, Liberia and Cameroon to the tropical districts of the Republics of Congo and Zaire (Hartley, 1988). Since the 14th century, palm oil has turned into a vital agricultural commodity, especially in Malaysia and Indonesia which has dominating this industry since the mid-1960s (Mukherjee and Sovacool, 2014). Henri Fauconnier and M. Adrien Hallet, a Belgian agronomist are credited to the development of the industry in Malaysia. Henri Fauconnier established the first commercial oil palm planting to replace an unsuccessful planting of coffee bushes at Tennamaram Estate on 1917 (Tate, 1996). Oil palm is a monocotyledonous plant, and unlike most other species, the only way to propagate is via tissue culture. It is a unique process which is undergoing callusing and embryogenesis processes and had been rigorously attempted in the 1960s through the 1970s (Kushairi et al. 2010). After a lot of attempted were made, it is reported that the earliest successful of oil palm tissue culture were in the mid 1970 (Jones, 1974; Rabechault and Martin, 1976). Although oil palm tissue culture process was successful, but there still issues appear. Corley et al. (1986) reported that in 1985, the first case of abnormality in clonal oil palm was presented in a colloquium organised by the International Society for Oil Palm Breeders (ISOPB). Mantled fruit and vegetative abnormalities caused a major furore among oil palm tissue culturists around world. This prompted a decrease in the hormone levels used or a total shirking of them at certain culture stages (Duval et al. 1988), or the total replacement of the chlorinated auxin, 2,4- dichlorophenoxyacetic acid (2,4-D) with a naphthalene acetic acid (NAA) (Sogeke, 1998). Over the last decade, more experiences and information on the tissue culture process have been accumulated and there was a renewed interest from around world to go ahead with the large-scale propagation of oil palm clones (Kushairi et al. 2006).